Prevalence of Puroindoline Genes and Their Impact on Quality Traits in A Diverse Germplasm of Wheat Genotypes - Mariam Khurshid; Munir Ahmad (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Grain hardness is an imperative attribute that determines the end-use quality of wheat. Variation in grain hardness is usually controlled by Puroindoline (pin-a and pin-b) genes located on the 5D chromosome. The study was aimed to reveal different mutations in Puroindoline genes utilizing the STS-marker approach and their association with important quality attributes in 100 hexaploid wheat genotypes (96 from Pakistan and 4 from CIMMYT). Overall, seven puroidoline genes were identified. Among them Pina-d1b(null) (85%) was most common while Pinb-d1i (1%) and Pinb-d1ab (1%) were most rare gene. Out of 100 genotypes, 97 had hard texture either with single or double mutant pin-genes, while three had a soft texture with wild type (Pinad1a/Pinb-d1a) pin-genes. All four quality attributes revealed a vast deviation among germplasm, while their correlation analysis revealed the highest association (r=0.71) between thousand-grain weight and protein content. In addition, three out of four quality traits, i.e. thousandgrain weight, SDS-sedimentation value and protein content, showed the highest mean values for double mutant (Pina-d1b/Pinb-d1b) followed by single mutant, i.e. Pina-d1b. The present study facilitates breeders for varietal selection (hard or soft) according to end-use quality and offers valuable information for improving wheat quality.